Studi Pengaruh Temperatur Aging terhadap Kekerasan Vickers, Ketahanan Impak, dan Korosi pada Aluminium Paduan - Wartono, Wartono; Rakhadani, Ihrom; Sumpena, Sumpena (Proklamasi 45 University, 2024)
Aluminum is a chemical element with the symbol Al with atomic number 13. Aluminum belongs to the light types of metals. Its electrical conductivity is 60% more than that of copper, so it is also used for electrical appliances. Aluminum is a reactive metal, so it is easily oxidized with oxygen. Aluminum is lightweight, strong, rust-resistant and malleable, aluminum is also utilized in many ways, such as materials for making fuselages, used in high-voltage cables and much more. This study aims to find out how temperature aging affects vickers hardness, impact toughness and corrosion in aluminum alloys. The aluminum used is 6000 series aluminum and is cut into workpieces according to ASTM standards. The applied method is by heat treatment precipitation hardening or age hardening. From the results of microstructure photo testing, it was found that the higher the aging temperature, the more amount of precipitation is formed and the distribution of precipitation is more even. However, when the heat treatment solution is performed, the precipitation decreases because at the same time the atomic void in thermal equilibrium at high temperature remains in place or a precipitate or so-called super saturated solute solution occurs. In hardness testing, the hardness continues to increase as the aging temperature increases and the maximum hardness is found at a temperature of 200oC with an average value of 86.6 kg/mm2. Meanwhile, the impact strength decreases with the increase in aging temperature and the highest impact strength at 120o C with a value of 0.619 j/mm2. In the corrosion test, as the temperature of aging increases, the aluminum is more resistant to corrosion the maximum value is obtained at 0.00251 mill/year at a temperature of 200o C.